ANALISIS PEMANGKU KEPENTINGAN PADA TINGGALAN ARKEOLOGI BAWAH AIR DI DESA BERAKIT - Stanov Purnawibowo (Balai Arkeologi Sumatera Utara, 2019)
The stakeholder analysis on the underwater archeological relics of Berakit village is an integrated part of the Research Program of Balai Arkeologi Medan, North Sumatra, entitled The Archeological Survey on the North Coast of Bintan Island, Bintan Regency, Riau Islands Province, that is conducted in 2018 in Berakit Village, Teluk Sebong District, Bintan Regency. The raised issue is the potential management of underwater relics in Berakit Village based on its stakeholder analysis. This study aims to obtain the policy of underwater archeological relics management based on the potential conflict that occurs among the stakeholders. The applied methods are in-depth interviews and Focused Group Discussion (FGD) with the stakeholders related to the underwater archeological relics in the research location. The stakeholders are classified into three groups, i.e. government, society, and academics. Issues on the underwater archeological relic management that give general descriptions about the potential conflicts of that archeological relic management are raised in the in-depth interviews and FGD. The potential is then analyzed using one of the conflict-analysis tools, i.e. onion analysis. The result of the stakeholder analysis shows a common need that becomes the knot of the conflict, i.e. the land utilization.